PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA LOLONG KABUPATEN PEKALONGAN - Carvi Eufrat Sativa,, Coriandri; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
This research is based on the issue of community participation in Desa Wisata Lolong. The purpose of this study is to analyze community participation in the development of Desa Wisata Lolong and describe the factors that influence community participation in its development. The theory used is the Ladder of Participation by Arnstein. The research method used is descriptive qualitative. Informants were selected using purposive sampling techniques. The analysis techniques include data reduction, data presentation, and data verification with the help of Atlas.TI software. The results show that the community of Lolong Tourism Village is at the placation level of participation, which is categorized as moderate participation. This is indicated by the community giving their aspirations, but decision- making is still controlled by the Village Head. The factors hindering participation include age, occupation, gender, stakeholder interference, and education level. The factors encouraging participation are willingness, ability, and opportunity. Two new factors were found: dependence on the season and tourism improving the community’s economy. The suggestion given is to delegate authority to the community.